Preconditioning Shields Against Vascular Events in Surgery (SAVES), a multicentre feasibility trial of preconditioning against adverse events in major vascular surgery: Study protocol for a randomised control trial - Healy D. (BioMed Central Ltd., 2018)
10.1186/s13063-015-0678-1